The DADYS-Screen: development and evaluation of a screening tool for affective dysregulation in children - Otto, Christiane; Kaman, Anne; Barkmann, Claus; Döpfner, Manfred; Görtz-Dorten, Anja; Ginsberg, Claudia; Zaplana Labarga, Sara; Treier, Anne-Katrin; Roessner, Veit; Hanisch, Charlotte; Koelch, Michael; Banaschewski, Tobias; et al. (Assessment, 2023)
Affective dysregulation (AD) in children is characterized by persistent irritability and severe temper outbursts. This study developed and evaluated a screening questionnaire for AD in children. The development included the generation of an initial item pool from existing instruments, a Delphi rating of experts, focus groups with experts and parents, and psychometric analyses of clinical and population-based samples. Based on data of a large community-based study, the final screening questionnaire was developed (n = 771; 49.7 % female; age M = 10.02 years; SD = 1.34) and evaluated (n = 8,974; 48.7 % female; age M = 10.00 years; SD = 1.38) with methods from classical test theory and item response theory. The developed DADYS-Screen (Diagnostic Tool for Affective Dysregulation in Children—Screening Questionnaire) includes 12 items with good psychometric properties and scale characteristics including a good fit to a one-factorial model in comparison to the baseline model, although only a “mediocre” fit according to the root mean square error of approximation (RMSEA). Results could be confirmed using a second and larger data set. Overall, the DADYS-Screen is able to identify children with AD, although it needs further investigation using clinical data.